Penggunaan Metode Bernyanyi untuk Meningkatkan Motivasi Belajar Peserta Didik Kelompok B TK Pusaka Ayah Bunda Desa Gereneng Kecamatan Sakra Timur - Husnul Laili (Pendidikan Al-Gafari, 2025)
This study aims to improve students' learning motivation by using the singing method. Children of various ages basically enjoy listening, singing and learning with songs/songs, especially at the early childhood education level which is very identical to songs/songs. This study is a Classroom Action Research (CAR) using qualitative methods. The research data were obtained using observation, interview and documentation techniques. The increase in students' learning motivation is marked by the increasing number of positive columns (yes) filled in each of the established indicators. The research results obtained were (1) Indicator